2021
DOI: 10.26444/aaem/125557
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity of children and adolescents from the Czech Republic, Hungary, Poland, and Slovakia: A systematic review

Abstract: Introduction and objective. Systematic monitoring of physical activity of young populations from different regions may be useful for making international comparisons, better understanding trends in physical activity and designing public health interventions to increase physical activity. Thus, the aim of the study was to comprehensively review studies examining the level of physical activity of children and adolescents from the Visegrád countries, and indicate the percentage of children and adolescents meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Chronic insufficient physical activity (PA) among adolescents has been observed across continents [1][2][3]. Insufficient PA among adolescents has been documented in summary reviews of the European Union countries [4,5] and regional studies in Visegrád countries, including the Czech Republic, Hungary, Poland, Slovakia [6], Germany [7], Sweden [8], and Slovenia [9], as well as in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic insufficient physical activity (PA) among adolescents has been observed across continents [1][2][3]. Insufficient PA among adolescents has been documented in summary reviews of the European Union countries [4,5] and regional studies in Visegrád countries, including the Czech Republic, Hungary, Poland, Slovakia [6], Germany [7], Sweden [8], and Slovenia [9], as well as in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The Health Behavior in School-aged Adolescents (HBSC) study reported that only 23.1% of boys and 14.0% of girls between the ages of 13 and 15 years adhered to the WHO’s PA recommendations [ 67 ]. In Central European countries (the Visegrad Group), the recommendations were met by 8.0–32.3% of adolescents in the Czech Republic, 8.5-14.6% of adolescents in Hungary, 7.5-69.4% of adolescents in Poland and 25.1% of adolescents in Slovakia [ 28 ]. The implementation of COVID-19 measures further reduced the time that adolescents engaged in PA [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to improve patterns of physical activity at the individual and population levels. Assessment of the level of physical activity of children and adolescents from the Visegrad countries -Czech Republic, Hungary, Poland, and Slovakia -showed that a large part of them, especially girls, did not comply with the recommendations regarding physical activity [46]. As far as school-age children are concerned, the COSI study [47] conducted in 2016 in 135 Polish schools showed that systemic and social solutions are necessary, both in rural and urban areas, in terms of infrastructure.…”
Section: Discussionmentioning
confidence: 99%